Cationic liposomes-DNA complexes as gene delivery vectors: Development and behaviour towards bone-like cells - Oliveira, A. C. (2009)
http://www.sciencedirect.com/science/article/B7GHW-4VNH426-1/2/25280834eb9207195153bdacda7196e8